2019
DOI: 10.1073/pnas.1816013116
|View full text |Cite
|
Sign up to set email alerts
|

Circuit-specific control of the medial entorhinal inputs to the dentate gyrus by atypical presynaptic NMDARs activated by astrocytes

Abstract: Here, we investigated the properties of presynaptic N-methyl-d-aspartate receptors (pre-NMDARs) at corticohippocampal excitatory connections between perforant path (PP) afferents and dentate granule cells (GCs), a circuit involved in memory encoding and centrally affected in Alzheimer’s disease and temporal lobe epilepsy. These receptors were previously reported to increase PP release probability in response to gliotransmitters released from astrocytes. Their activation occurred even under conditions of elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 72 publications
2
63
1
Order By: Relevance
“…Nevertheless, our findings make it clear that there is a maturation-associated shift from the involvement of NMDARs to mGluRs in hippocampal plasticity. Forms of preLTP that are dependent on preNMDARs have been described in the hippocampus 41 and at entorhinal cortex to DG synapses [48][49][50][51] and preLTP forms independent of NMDARs have also been described at hippocampal MF-CA3 synapses 52 , in the cerebellum 53 , thalamus 54 , subiculum 55 , amygdala 56 , and neocortex 57 . The requirement of mGluRs for some forms of preLTP has previously been defined in the hippocampus 45,47 , although these preLTPs were not induced using STDP protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our findings make it clear that there is a maturation-associated shift from the involvement of NMDARs to mGluRs in hippocampal plasticity. Forms of preLTP that are dependent on preNMDARs have been described in the hippocampus 41 and at entorhinal cortex to DG synapses [48][49][50][51] and preLTP forms independent of NMDARs have also been described at hippocampal MF-CA3 synapses 52 , in the cerebellum 53 , thalamus 54 , subiculum 55 , amygdala 56 , and neocortex 57 . The requirement of mGluRs for some forms of preLTP has previously been defined in the hippocampus 45,47 , although these preLTPs were not induced using STDP protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Preembedding immunogold analysis lends key experimental support. While previous work found GluN3a-NMDARs at postsynaptic and extrasynaptic plasma membranes (5), Savtchouk et al (3) observed that on MPP axons, the majority of GluN3a immunogold particles are presynaptic. GluN3a particles were located away from the synaptic cleft, closely apposed to astrocytic membranes, and were virtually absent from LPP axons.…”
mentioning
confidence: 84%
“…As mentioned, one commonality of pre-NMDARs is their strategic location at subsets of synapses to control the induction of time-restricted or circuit-specific forms of short-or long-term plasticity. Expanding on this literature, Savtchouk et al (3) report that LTP is enhanced at GluN3a-null MPP-GC synapses and suggest that GluN3a-pre-NMDARs impose a basal "prepotentiation" state that narrows the dynamic range for LTP induction. Blocking Ca 2+ elevation in astrocytes by loading the Ca 2+ chelator 1,2-Bis(2-aminophenoxy)ethane N,N,N′,N′-tetraacetic acid (BAPTA) recapitulated the enhanced LTP, suggesting a role for pre-NMDAR-astrocyte coupling in this modulation.…”
mentioning
confidence: 98%
See 2 more Smart Citations